2020
DOI: 10.1007/s10805-020-09376-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Attitudes of Portuguese Accounting Students and Professionals Towards Earnings Management

Abstract: We revisit religiosity, gender, age, ethics education and experience as drivers of ethicality, while expanding prior research from Anglo-Saxon and Asiatic/Euro-Asiatic countries to a Latin European country, Portugal. We apply the Merchant (1989) instrument of attitudes towards earnings management, in a sample of Portuguese accounting students and alumni. We find no significant evidence of a positive association between religiosity and accountants' judgments on earnings management. However, gender, age, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 109 publications
2
19
0
1
Order By: Relevance
“…Thus, in the data analysis 159 valid answers were considered. As such, it is a convenience sample and not a probabilistic sample, but considered valid in previous studies (Cepêda and Monteiro, 2020;Montenegro and Rodrigues, 2020;Tassadaq and Malik, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in the data analysis 159 valid answers were considered. As such, it is a convenience sample and not a probabilistic sample, but considered valid in previous studies (Cepêda and Monteiro, 2020;Montenegro and Rodrigues, 2020;Tassadaq and Malik, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Cepêda and Monteiro (2020) concluded that a certified accountant´s characteristics influence FI usefulness perceptions. In the study of Montenegro and Rodrigues (2020), applied in Portugal, the gender, age, education (and accounting ethics education), and experience influence of accountants' judgments. Thus, the seventh and last research question is posed.…”
Section: Rq6 What Corporate Governance Mechanisms Can Mitigate Aemp?mentioning
confidence: 99%
See 2 more Smart Citations
“…During the period mentioned, 389 complete observations were obtained. Given the high number of Portuguese companies, a non-probabilistic sample was chosen, which is practical in scientific studies covering a very large population [55,56].…”
Section: Figure 1 Research Modelmentioning
confidence: 99%